Assessing Financial Distress Drivers: Financial Metrics and Corporate Practices in Indonesian Manufacturing Companies - Fazila, Paula (Indonesian Journal of Sustainability Policy and Technology, 2024)
Understanding the factors that contribute to financial distress is crucial for assessing the financial health of companies. This research examines, validates, and analyses the influence of leverage, liquidity, profitability, sales growth, good corporate governance (GCG), and corporate social responsibility (CSR) on financial distress. The study utilizes secondary data derived from financial statements. The sample consists of 310 financial reports from manufacturing companies listed on the Indonesia Stock Exchange (IDX) over five years (2015-2019), selected through purposive sampling. Logistic regression analysis was applied in this study. The findings indicate that leverage, liquidity, profitability, and CSR significantly impact financial distress. In contrast, sales growth and GCG do not substantially affect financial distress. These results suggest that companies should focus on managing leverage and liquidity while enhancing profitability and CSR practices to mitigate financial distress risks. On the other hand, policymakers need to establish regulations and incentives that encourage responsible financial management and social responsibility initiatives. It is important to prevent financial distress and provide a direction for companies and policymakers to enhance financial stability and sustainability.